2000
DOI: 10.1017/s0954102000000195
|View full text |Cite
|
Sign up to set email alerts
|

Weaning mass and the future survival of juvenile southern elephant seals, Mirounga leonina, at Macquarie Island

Abstract: Seals that survived their first year were on average 2% and 4% heavier at birth and at weaning than the "non-survivors". First year survival rates calculated for weaners over 135 kg weaning masses showed these weaners had hgher survival rates than those less than 95 kg at weaning (71.55% and 54.15% respectively). Heavy weaners had greater fat reserves than light weaners and gained relatively more mass during lactation. Size, and therefore condition at weaning, influences first year survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
193
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(209 citation statements)
references
References 27 publications
7
193
1
Order By: Relevance
“…Relying only on coastal, benthic prey of poor nutritional quality will be useful to reduce the foraging trip length and hence the pup mortality during early lactation. However, this foraging strategy will negatively affect the pup growth rate and may increase the mortality rate at weaning if the weight at weaning correlates with the survival rate, as reported for other pinnipeds (McMahon et al, 2000).…”
Section: Discussionmentioning
confidence: 87%
“…Relying only on coastal, benthic prey of poor nutritional quality will be useful to reduce the foraging trip length and hence the pup mortality during early lactation. However, this foraging strategy will negatively affect the pup growth rate and may increase the mortality rate at weaning if the weight at weaning correlates with the survival rate, as reported for other pinnipeds (McMahon et al, 2000).…”
Section: Discussionmentioning
confidence: 87%
“…For small weanlings, . Given that an extra 5 kg may sustain a fasting pup for 10 days at sea [19], this difference is biologically significant. Females foraging at high (inferred from smaller d 13 C values) or low (inferred from larger d 13 C values) latitudes, had a greater probability of weaning a large pup than females foraging in the interfrontal zone (figure 2a and electronic supplementary material, figure S1).…”
Section: Results (A) Stable Isotopesmentioning
confidence: 99%
“…McMahon et al [19] found a positive relationship between a pup post-weaning survival and its weaning mass: females that have stored and transferred more energy to their pup prior to the spring haul-out had a larger reproductive fitness. Because any changes in patterns of maternal foraging strategies may affect pup survival, we assessed the effect of maternal foraging strategies on pup fitness by studying the relationships between pup weaning mass and blood isotope ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Body size is a strong predictor of infant and juvenile survival in a wide range of animals, including some lizards (80), fish (81), birds (82,83), rodents (84,85), pinnipeds (86,87), deer (88,89), and primates (90). Although these effects are often attributable to predation, similar effects are seen in humans, for which both low birthweight and poor growth compromise long-term health and well-being (91)(92)(93)(94).…”
Section: Discussionmentioning
confidence: 99%